Fibre Bragg Grating Based Strain Sensors: Review of Technology and Applications - Carlo Edoardo Campanella; Antonello Cuccovillo; Clarissa Campanella; Abdulkadir Yurt; Vittorio M. N. Passaro (Sensors, 2018)
Fibre Bragg grating (FBG) strain sensors are not only a very well-established research field, but they are also acquiring a bigger market share due to their sensitivity and low costs. In this paper we review FBG strain sensors with high focus on the underlying physical principles, the interrogation, and the read-out techniques. Particular emphasis is given to recent advances in highly-performing, single head FBG, a category FBG strain sensors belong to. Different sensing schemes are described, including FBG strain sensors based on mode splitting. Their operation principle and performance are reported and compared with the conventional architectures. In conclusion, some advanced applications and key sectors the global fibre-optic strain sensors market are envisaged, as well as the main market players acting in this field.